Effect of source-sink manipulation on yield and related yield components in cassava, Manihot esculenta Crantz - Amarullah, -; Indradewa, D; Yudono, P; Sunarminto, BH Dan (International Journal of Agricultural Research, Innovation and Technology, 2017)
The distribution of nutrients and assimilates in different organs and tissues is in a constant state of flux throughout the growth and development of a plant. At key stages during the life cycle, profound changes occur, and perhaps one of the most critical of these is during tubers filling. The purpose of this study was to examine the effect of sources- sink manipulation to related yield and yield components of cassava cultivars Singgah. Experiment manipulation source using number of branches cropping (S) which consists of three levels i.e. S1: 1 branch planting; S2: 2 branches planting; S3: 3 branches planting and manipulation at the bottom of that manipulation of the bottom with the model sliced the bottom of the cuttings (L) which consists of three levels i.e. L1: Sliced flat cuttings; L2: Sliced oblique cuttings; L3: Sliced cuttings of two sloping sides. In the cassava plant there is a relationship between the source and the bottom. Manipulation treatment plant cassava with two branches crop resources, if interaction the bottom with the model manipulation cuttings incision flat base capable of increasing biomass as well as the amount of cassava tuber crop plant varieties Singgah. The diameter of the tubers if interaction with wedge base model of cuttings oblique slices one general interaction and manipulation of two branches crop with all models of the base of the cuttings slice significantly improves weight of tuber crop. Int. J. Agril. Res. Innov. & Tech. 6 (2): 69-76, December, 2016